LZS/Al2O3 Glass-Ceramic Composites Sintered by Fast Firing - Arcaro,Sabrina (2017)
In this work, nanometric Al2O3 (1-5 vol.%) particles (13 nm, 100 m2/g) were added to a 19.58Li2O•11.10ZrO2•69.32SiO2 (mol%) (3.5 µm, 2.5 m2/g) parent glass-ceramic matrix to prepare composites with the purpose of studying the influence of Al2O3 on their structure, microstructure, mechanical, thermal and electrical properties when sintered by fast firing. The parent glass-ceramic was prepared by melting and fast cooling (in water) to obtain a glass frit. The resulting glass frit was milled according to a two-step procedure consisting on a dry milling stage followed by a long wet milling step down. Each composition was wet homogenized and then dried at 110 ºC for 48 h for disaggregation. The obtained powders were uniaxially pressed (100 MPa) and compacts sintered by fast firing (175 ºC/min) between 800 and 900 ºC for 30 min. The composites, with relative densities ranging from 89% to 93%, showed zircon and β-spodumene as main crystalline phases. The hardness and Young's modulus varied from 4.5 to 6.5 GPa, and from 65 to 102 GPa, respectively. The formation of β-spodumene in the obtained composites leads to reduce the CTEs, whose values ranged from 13 to 7 x 10-6 ºC-1.